Veterinary practitioners’ selection of diagnostic tests for the primary evaluation of colic in the horse - Curtis, L.; Trewin, I.; England, Gary C.W.; Burford, J.H.; Freeman, S.L. (BMJ Publishing Group, 2015)
The aim of this study was to survey veterinary practitioners’ selection of diagnostic tests for horses with clinical signs of abdominal pain. A questionnaire was distributed to veterinary surgeons involved in the primary evaluation of horses with abdominal pain, including the respondent's demographics, selection of diagnostic tests and factors affecting decision-making. Data analysis included descriptive analysis, categorisation of free text and simple univariable correlations to explore the relationships between independent variables and the relative self-estimated frequency that diagnostic tests were performed. A total of 228 responses were analysed. Participants worked in mixed practice (55.7 per cent), first opinion equine (22.8 per cent), first and second opinion equine (17.9 per cent) and referral practice (3.1 per cent). The majority (48.2 per cent, 105/218) were very confident managing a colic case (confidence level 4/5). The most frequently used diagnostic tests were ‘response to analgesia’ (87.2±24.0 per cent cases), rectal examination (75.9±21.2 per cent) and nasogastric intubation (43.8±27.6 per cent). Approach varied between practitioners, and for all diagnostic tests with frequency of use ranging from 0 to 100 per cent of cases. ‘Risk to personal safety’ was the most common reason for not using rectal examination. Practitioner's opinion of their confidence level in managing a colic case was associated with how frequently they used different diagnostic tests. There was marked variation in practitioners’ approaches, highlighting the need for further evidence to support decision-making.